The Charter, General Ordinances, etc., of the City of Evansville Page 230 § 23 - (:unkn) unknown (General Publisher, 1871)
Prohibited keeping any gun or blasting powder in quantities greater than twenty-five pounds at one time. Also prohibited keeping such quantities in any other vessel than a tin canister, with a cover or stopper and the words "Gun Powder" labeled on it. Also prohibited selling gun powder after twilight.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER